Didaktika matematiky se zaměřením na specifické poruchy učení - Blažková, Růžena (Matematika a didaktika matematiky, 2017)
Title in English: Didactics of mathematics with a focus on specific learning disorders Problems of specific learning difficulties is the centre of interest of teachers, especially the point of view of inclusive education of pupils. Problems of specific learning difficulties is at the centre of interest of teachers, especially, from the point of view of inclusive education of pupils. In the article, there is a classification of difficulties, causes of difficulties in mathematics, analysis of particular elements phenomen of mathematics in primary school. The article is aimed at problems of children in the area of natural numbers, decimals, whole numbers and fractions.